PENGELOLAAN KOMUNIKASI PARIWISATA DALAM MENINGKATKAN KUNJUNGAN WISATAWAN PANTAI KONENG MEDANG KAMPAI KOTA DUMAI - Aisyah Aldi Saputri; Nurjanah ' (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Koneng Beach is one of the seaside tourist attractions in Medang Kampai District, Dumai City. An area directly facing Malaysia with attractive marine tourism potential. Starting from 2017, Koneng Beach has been successfully visited by hundreds of thousands of visitors with its natural attractions, implementation of tourism communications, and all the supporting facilities that support tourists in visiting Koneng Beach. The aim of this research is to analyze tourism communication and managerial communication management in increasing tourist visits to Koneng Medang Kampai Beach, Dumai City. This research uses a qualitative approach. Data collection techniques through interviews, observation and documentation. The data examination technique uses triangulation. The results of this research show that the tourism communication activities carried out to increase tourist visits to Koneng Medang Kampai Beach, Dumai City involve the management, government and also tourists as communicators. Message management is informative and communicative, using social media such as Tiktok and Facebook, online media such as the official DISKOPAR website and using print media in the form of brochures and banners. The general public is involved as communicants with feedback from Koneng beach tourism becoming known. Management in developing tourist destinations is very good in increasing tourist visits. Keywords: Communication Management, Tourism Communication, Beaches, Tourists, Koneng Beach